Comparison of Endothelial Cell Loss after Phacoemulsification Surgery between Patients with Diabetes Mellitus and Non-Diabetic Patients at Kariadi Hospital: A Prospective Study: Oral Presentation - Observational Study - Resident - Nugraha Adiyasa; Wisnu Sadasih; A. Rizal Fanany (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : To compare the endothelial cell loss after phacoemulsification surgery in patients with DM and non- DM patients Methods : This was a prospective study conducted at Kariadi Hospital, Semarang, Indonesia. A total of 20 eyes of 20 patients (10 DM and 10 non-DM) who underwent phacoemulsification surgery were included in this study. The central corneal thickness (CCT), endothelial cell density (ECD), coefficient of variation (CV), and hexagonality (HEX) were measured preoperatively and on day-7 postoperatively. The percentage of endothelial cell loss (%ECL) was calculated and compared between the two groups. Results : The mean pre-operative and post-operative CCT was similar in both groups (DM =546.6±44.26μm, non-DM=516.7±42.2μm, p=0.949 ;DM=562.8±46.1μm, non-DM=533.7±46.6μm, p=0.997). The mean percentage of endothelial cell loss was slightly higher in the DM group compared to the non- DM group but not significant (6.66±2.36% vs. 2.31±1.72%, p=0.566). There were no significant differences between the CV and HEX on pre-operative and day-7 after surgery Conclusion : Patients with DM have a slightly higher percentage of endothelial cell loss after phacoemulsification surgery compared to non-DM patients. The mean CCT, CV and HEX pre-operation and day-7 were quite similar in both groups. These findings suggest that patients with DM may require more careful monitoring and follow-up after phacoemulsification surgery.